The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/s0102-69922016000100008
|View full text |Cite
|
Sign up to set email alerts
|

Novos padrões de investigação policial no Brasil

Abstract: Resumo: Neste artigo, descrevemos algumas das principais características dos casos de investigação policial que foram denunciados pelo Ministério Público Estadual. O padrão que emerge dos dados da pesquisa realizada em nove estados brasileiros, a partir de uma amostra dos processos criminais arquivados em 2011, difere das representações tradicionais da investigação baseada na busca de testemunhas e produção de depoimentos e confissões. As prisões em flagrante ocupam lugar de destaque na instrução criminal e te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
(6 reference statements)
0
4
0
1
Order By: Relevance
“…Recent studies confirm this prediction, as those with criminal records are more likely to be arrested, held in pretrial detention, and convicted (Kurlychek & Johnson, 2019;Kutateladze & Lawson, 2017). In Brazil, defendants with previous criminal records have greater odds of surviving throughout the flow of the criminal justice system (Vargas, 2014), being more prone to pretrial detention (Jesus Filho, 2017), charges (Ribeiro & Lima, 2020), and convictions (Ribeiro, 2010) for all types of offenses (Costa & de Oliveira Júnior, 2016). Gottfredson and Hindelang (1979) understand that social control exercised in the subjects' private life could also be measured by the place and time where crimes happen.…”
Section: Introductionmentioning
confidence: 93%
“…Recent studies confirm this prediction, as those with criminal records are more likely to be arrested, held in pretrial detention, and convicted (Kurlychek & Johnson, 2019;Kutateladze & Lawson, 2017). In Brazil, defendants with previous criminal records have greater odds of surviving throughout the flow of the criminal justice system (Vargas, 2014), being more prone to pretrial detention (Jesus Filho, 2017), charges (Ribeiro & Lima, 2020), and convictions (Ribeiro, 2010) for all types of offenses (Costa & de Oliveira Júnior, 2016). Gottfredson and Hindelang (1979) understand that social control exercised in the subjects' private life could also be measured by the place and time where crimes happen.…”
Section: Introductionmentioning
confidence: 93%
“…In Brazil, scholars have shown that homicides between strangers are less likely to be cleared (Costa, 2015), unless the suspect is caught red-handed (Costa & Oliveira Júnior, 2016). The relationship is also an important predictor of the final disposition, as murders involving family members are less likely to receive harsh punishment than other deaths (Azevedo & Sinhoretto, 2018).…”
Section: Morphologymentioning
confidence: 99%
“…In Brazil, studies on homicide clearance conclude that the successful identification of suspects is related to the efficiency of certain procedures deployed by the police (Costa & Oliveira Júnior, 2016). The first being the arrest in flagrante delicto , which involves the suspect’s immediate capture and the collection of information essential to opening the police inquiry, which will allow charges to be brought into the criminal court (Costa, 2015).…”
Section: Legal Factors and Police Procedures As Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Análises de casos denunciados ao Ministério Público mostram que pouco mais da metade dos acusados em crimes de homicídio foram presos em flagrante, ou seja, a prisão não resultou de uma investigação criminal (Costa & Oliveira, 2016). Além disso, há aqueles que olham a investigação pela lente do inquérito policial, atribuindo a esse elemento um papel central na formação de culpa de grupos específicos de pessoas (Kant de Lima, 1995;Misse, 2010a).…”
Section: Introductionunclassified